Inflammatory processes and schizophrenia: two independent lines of evidence from a study of twins discordant and concordant for schizophrenic disorders - Braun, Silke; Weisbrod, Matthias (European archives of psychiatry and clinical neuroscience, 2017)
The concept of twin concordance involves quantifying the resemblance between co-twins in an “objective” and reproducible way. Yet, quantifying resemblance in the case of complex psychiatric traits like schizophrenic disorders leads to methodological problems, as the yes-no dichotomy of diagnostic schemata does not allow one to assess between-subject differences in psychopathology patterns sufficiently accurately. Therefore, we relied on a multidimensional, quantitative concordance measure that provided a high resolution and differentiation when assessing the resemblance of psychopathology patterns. This concordance measure was central to our investigations into the potential link between schizophrenic disorders and aberrancies of the inflammatory response system. Specifically, we aimed to determine the extent to which (1) the observed variation of between-subject psychopathology concordance among 100 schizophrenic patients and (2) the observed variation of within-pair psychopathology concordance among 71 twin pairs can be explained by immunoglobulin M (IgM) levels. To accomplish this goal, we had to “gauge” in a first step the concordance measure’s performance by (1) comparing the psychopathology patterns of 269 index cases suffering from functional psychoses with the respective patterns of the 350 “affecteds” among their first-degree relatives; (2) systematically comparing the psychopathology patterns of 100 unrelated patients with a diagnosis of schizophrenic disorders with each other; and (3) detailing the within-pair concordance of elementary traits among 2734 healthy twin pairs. As to the role of active immune processes in the context of schizophrenic disorders, we found that there exists a 20-30% subgroup of patients for whom aberrancies of the inflammatory response system, as quantified through IgM levels, appeared to be linked to the pathogenesis of schizophrenic disorders (r = 0.7515/0.8184, p < 0.0001). The variation of within-pair psychopathology concordance among twins with schizophrenic disorders was found to be “explainable” in part by chronically elevated IgM levels (24.5% of observed phenotypic variance; p = 0.0434), thus suggesting that monozygotic twins concordant for schizophrenic disorders may possess a less “robust” variant of the inflammatory response system which can more easily be triggered by exogenous factors than the more “robust” variants of discordant pairs. Though the underlying biological mechanisms remain to be detected, our data have cleared the way for an early identification of patients with schizophrenic disorders for whom the inflammatory response system may be a target for therapeutic intervention. Moreover, our results will likely lead to new treatment strategies that involve elements of personalized medicine.
First online: 04 April 2017
Gesehen am 21.06.2018